Construct validation of teacher efficacy in teaching Arabic scale: a co-variance based approach - Mohamed Adnan, Mohamad Azrien; Mamat , Arifin; Ahmed Mohamed, Ismaiel Hassanein; Ibrahim, Mohd Burhan (Institute of Research Engineers and Doctors, 2016)
The first attempt of this study is to investigate teacher efficacy construct. In so doing, this study tries to develop the extent to which the conceptualized teacher measure reproduces the data. Second, this study evaluates the adequacy of the teacher efficacy measure across teacher’s place of graduation. The data were collected from adopted version of Teachers’ Sense of Efficacy Scale administered to 252 teachers of National Religious Secondary School in Malaysia. The results of confirmatory factor analysis supported the adequacy of teacher efficacy measure and found that teacher is a multidimensional construct with four underlying dimensions. The model also found to be applicable across teacher’s place of graduation